Moral Education of Students In The Culture of The Words Please, Sorry, Thank You and Excuse In Natural Schools - Muttaqin, Muhammad Fauzan; Raharjo, Tri Joko; Suharini, Erni; Wagiran, Wagiran (Proceedings of International Conference on Science, Education, and Technology, 2024)
This research aims to explore students' moral education through cultivating the use of the words "please", "sorry", "thank you", and "excuse me" at Alam Tangerang Elementary School. The problem underlying this research is the low awareness and application of moral values in students' daily interactions. The main aim of this research is to understand how these words can shape students' moral behavior and assess the effectiveness of educational strategies implemented by schools. The research methodology used is a qualitative approach with a case study design. The research subjects consisted of students, teachers and principals at Alam Elementary School. Data collection was carried out through participant observation, in-depth interviews, and document analysis. Data validation was carried out using triangulation techniques to ensure data accuracy through various sources and data collection methods. Data analysis was carried out through the process of coding, categorization and drawing thematic conclusions. The results of the research show that moral education at Alam Elementary School has succeeded in cultivating the use of the words "please", "sorry", "thank you" and "excuse me" among students. The use of these words appears to have increased significantly in students' daily interactions, both inside and outside the classroom. Teachers and principals play an important role in instilling these values through behavioral modeling, positive reinforcement, and integration in learning activities. The implication is that moral education that focuses on the use of polite words has a positive impact on the development of students' character.